Makna Filosofis dan Saintifik Terkait Janji dan Ancaman (al-Jannah wa Al-Nar) - Ali, Muhdi; Masbuang, Masbuang; Romadhony, Nagib; Rosa, Andi (Pondok Pesantren Hamalatul Qur'an Jogoroto Jombang, 2024)
This research discusses the philosophical and scientific meaning of the concepts of promises and threats in a religious context, especially in Islamic teachings regarding al-Jannah (heaven) and al-Nar (hell). Allah's promises regarding rewards for individuals who believe and do good deeds function as moral motivation, while threats against violators of moral norms function to prevent bad behavior. With a qualitative approach that discusses relevant literature, this research explores the interaction of these two concepts in shaping social norms and individual morality. The research results highlight that the synergy between promises and threats is not only powerful in regulating individual behavior, but also provides a deep perspective on moral and spiritual responsibility. A strong understanding of promises and threats can help individuals make wiser decisions in accordance with religious teachings, as well as build good character. These findings imply the importance of moral and spiritual education to increase people's awareness in living a life that adheres to good ethical values ​​and social responsibility. This research also shows that clear promises and threats can encourage harmonious social development and reduce the potential for conflict in society.